Women Empowerment in Netflix Series Unbelievable - Anggita Riana Dewi; Yulistiyanti; Katharina Rustipa (Metathesis: Journal of English Language, Literature, and Teaching, 2022)
This research aims to reveal how Unbelievable portrays the differences between male and female detectives handling rape cases, to find out Duvall’s, the female detective, factors, and motivation in helping women victims, and to find out the values ​​of women empowerment in Unbelievable. The research used qualitative method. Reader response, subjective criticism, and women empowerment were the bases theories used in the research. The data are sentences and conversations that show differences in treatment, mindset, factors and motivation, as well as the empowerment of the female main character. There are three results of this study; (1) three differences covering the victim treatment, investigation model, and the mindset between male and female detectives handling rape cases; sensitivity to the mental condition of the victim, clarity of providing investigative information, the efficiency of the investigation system, and assessment of the case and rape victims. (2) Duvall's factors and motivation include self-confidence, empathy, protestant work ethic, and Christian faith. (3) Duvall's success in bringing justice has given strength to victims and other values ​​such as economic independence, freedom to get an education and career paths, balance roles at home and at work, are a reflection of women empowerment.